The Effect of Supplemental Oxygen on Hypoxemia and Hypercapnia in COPD Patients with Acute Respiratory Failure (Annals of Medical Research, 2021)
None
Keywords: COPD, Supplemental oxygen therapy, Hypoxemia, Hypercapnia.